Compartment syndrome of the arm after surgery for a supracondylar fracture of the humerus - Liñán-Padilla, Alejandro; Rodriguez-Fernández, Francisco Manuel (Revista Colombiana de Ortopedia y Traumatología, 2022)
We present a compartment syndrome in the arm that is a very rare location and for which there is hardly any bibliography. The case presented 48 hours after humerus surgery through a posterior approach, although it affected the anterior compartment. With this case we want to highlight the importance of the differential diagnosis in an uncommon location.